Learning Strategy to Improve Student Learning Activities in PAI Learning in SMP Al-Huda Sedayulawas Brondong Lamongan - Dina Mawaddatur Rohmah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
This study aims to discuss how the application of Learning Strategies in PAI learning in SMP al-Huda Sedayulawas Brondong Lamongan. In this study, researchers used descriptive qualitative research. The data collection is done by observation, documentation and interviews, while the data analysis uses inductive, deductive and comparative methods. Based on the results of the study, it can be concluded: First, Think, Talk, Write Strategies are applied in SMP al-Huda Sedayulawas Brondong Lamongan by forming groups that each must be able to present the content of the verse, recitation of recitation in the verse. Each group must be active in this activity because the students' score is obtained from the points given by the teacher during the discussion and question and answer session. The implementation of this strategy did not experience significant problems or obstacles, the Think, Talk, Write strategy has given very satisfying results, in addition to this strategy also uses several methods including lectures, questions and answers, and others in the learning process; Second, by using the Think, Talk, Write strategy, it can be said that students' learning activeness is good, because the children have fulfilled some of the indicators of learning activeness, are more enthusiastic and more enthusiastic. Keywords: Learning Strategies, Student Learning Activity, PAI